Technology Applications through Cooperative Learning in Visual Arts Education among Students in Inclusive Education Programs: A Fuzzy Delphi Approach; [Aplikasi Teknologi melalui Pembelajaran Koperatif dalam Pendidikan Seni Visual di kalangan Murid Program Pendidikan Inklusif: Pendekatan Fuzzy Delphi] - Mohd Zahuri Khairani (Tanjung Malim, 2024)
Technology Applications through Cooperative Learning in Visual Arts Education among Students in Inclusive Education Programs: A Fuzzy Delphi Approach; [Aplikasi Teknologi melalui Pembelajaran Koperatif dalam Pendidikan Seni Visual di kalangan Murid Program Pendidikan Inklusif: Pendekatan Fuzzy Delphi] by Mohd Zahuri Khairani